2015
DOI: 10.11114/afa.v1i2.850
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the Risk-taking Behavior of Commercial Banks in Bangladesh

Abstract: This study examines the capital regulation, profitability, bank size, liquidity, off-balance sheet activities, charter value, dividend payout ratio and macroeconomic variables as determinants of bank risk (credit risk and overall risk) by using information from 30 Bangladeshi commercial banks over a period of [2005][2006][2007][2008][2009][2010][2011][2012][2013]. We use Generalized Methods of Moments (GMM) in an unbalanced dynamic panel data framework. The empirical results show a negative relation between cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Liquidity (liq) is the ratio of total loans to total deposits and indicates the extent to which customer loans are financed by customer deposits. Higher values reflects higher liquidity risk (Dong et al, 2014;Rahman et al, 2015).…”
Section: Variables Definitionmentioning
confidence: 99%
“…Liquidity (liq) is the ratio of total loans to total deposits and indicates the extent to which customer loans are financed by customer deposits. Higher values reflects higher liquidity risk (Dong et al, 2014;Rahman et al, 2015).…”
Section: Variables Definitionmentioning
confidence: 99%
“…Thus, OBS activities include items such as letters of credit, unfunded loan commitments, lines of credit, and derivatives. And this can increase banks risk, which supported by Angbazo [10] and Rahman et al [52] findings. However, it been argued that OBS activities increase banks profitability, which allows them to expand their leverage and maximize the return on investment.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 71%
“…In addition, large banks are forced to generate more profit as a result it will take more risks also, large banks are convinced that they will be bailed out by governments because they are "too-big-to-fail" and this encourage large banks to take more risks. The study conducted by Kane [36] and Rahman et al [52] reported a positive link between risk and size. Based on these arguments the following hypothesis may be formulated:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, a parking facility, token system and good interior designing, thus, can influence the customer to choose a bank. According to Rahaman, Murad, and Asaduzzaman (2015), physical facilities play an important role in choosing a bank. Conceptual Framework: The concept of this model was to analyse the factors determining customers' choices based on different qualitative factors regarding services and service quality based on customers' perception.…”
Section: Literature Reviewmentioning
confidence: 99%